Genotype X Environment interaction of mosaic disease, root yields and total carotene concentration of yellowfleshed cassava in Nigeria - Maroya, N.; Kulakow, Peter A.; Dixon, A.; Maziya-Dixon, B.B. (Hindawi Limited, 2012)
Twenty-one yellow-fleshed cassava genotypes were evaluated over two years in five major cassava growing agroecological zones in Nigeria. The trials were established in a randomized complete block design with four replications to assess genotype performance and Genotype × Environment interaction for cassava mosaic disease (CMD), fresh and dry root yield (FYLD; DYLD), root dry matter content (DMC), and total carotene concentration (TCC). Combined analysis of variance showed significant differences () among genotypes (G), environment (E), and Genotype × Environment interaction (GE) for all the traits tested. For reaction to CMD, the best genotypes showing stable resistance were TMS 07/0539 and TMS 07/0628. For root yield, the best genotypes were TMS 01/1368 and TMS 07/0553. Genotype TMS 07/0593 was the best for DMC and TCC across the 10 environments. Variation among genotypes accounted for most of the Total Sum of Squares for CMD (72.1%) and TCC (34.4%). Environmental variation accounted for most of the Total Sum of Squares for FYLD (42.8%), DYLD (39.6%), and DMC (29.2%). This study revealed that TMS 07/0593 has the highest and most stable TCC, DMC with the lowest CMD severity score and appeared to be the best genotype.